The Role of CXCR3 in Nervous System-Related Diseases - Fangyuan Wang; Bing Guo; Ziyang Jia; Zhou Jing; Qingyi Wang; Minghe Li; Bingqi Lu; Wulong Liang; Weihua Hu; Xudong Fu (Mediators of Inflammation)
Inflammatory chemokines are a group of G-protein receptor ligands characterized by conserved cysteine residues, which can be divided into four main subfamilies: CC, CXC, XC, and CX3C. The C-X-C chemokine receptor (CXCR) 3 and its ligands, C-X-C chemokine ligands (CXCLs), are widely expressed in both the peripheral nervous system (PNS) and central nervous system (CNS). This comprehensive literature review aims to examine the functions and pathways of CXCR3 and its ligands in nervous system-related diseases. In summary, while the related pathways and the expression levels of CXCR3 and its ligands are varied among different cells in PNS and CNS, the MPAK pathway is the core via which CXCR3 exerts physiological functions. It is not only the core pathway of CXCR3 after activation but also participates in the expression of CXCR3 ligands in the nervous system. In addition, despite CXCR3 being a common inflammatory chemokine receptor, there is no consensus on its precise roles in various diseases. This uncertainty may be attributable to distinct inflammatory characteristics, that inflammation simultaneously possesses the dual properties of damage induction and repair facilitation.